The Disablement Process: A Conceptual Framework for Dementia-Associated Disability - Barberger-Gateau, P.; Fabrigoule, C.; Amieva, H.; Helmer, C.; Dartigues, J.F. (Dementia and geriatric cognitive disorders, 2002)
Most of the social and economic burden of dementia is attributable to its consequences in terms of disability. In this review, we describe the concepts defined in the disablement process model of Verbrugge and Jette [Soc Sci Med 1994;38:1–14] and show how they apply to dementia. The main pathway leads from pathology to impairments, functional limitations and disability. Pathologies (any cause of dementia) are expressed by impairments in specific cognitive processes. Functional limitations are limitations in generic cognitive tasks such as remembering a list of words or orientating oneself in time and space. They are responsible for disability in activities of daily living. Predisposing risk factors as well as introduced intraindividual and extraindividual factors speed up or slow down the main pathway. We show how the model can help in understanding the functional consequences of dementia, for better assessment and management of demented subjects.